Toxicological evaluation of cabbage extracts using fertile duck embryos - Quidlat, Arlene Marie S.; Dumelod, Benelyn Domingo (1999., 1999)
Cabbage is a widely consumed commodity in the Philippines, being available year-round at affordable prices. People with large intakes of cabbage are at risk of toxicity, since it contains glucosinolates which exhibit antithyroid activity by inhibiting iodine uptake by the thyroid, thereby, impairing the synthesis of the thyroid hormones which play important roles in the metabolic processes of the body. The study aimed at evaluating the relative toxicities of raw, half-cooked and cooked cabbage. Toxicological evaluation was carried out on five-day old fertile duck embryos. Extracts of raw, half-cooked and cooked cabbages were used in Treatments A, B and C, respectively. Two sets of control --- open and closed --- were used and these were uninoculated. The mean percentage mortality for both sets of control was 5% while for Treatments A, B and C, the values were 98.33%, 100% and 96.67%, respectively. Results showed that at α = 0.05, the three treatments of cabbage were not significantly different from each other but were significantly different from the controls, implying that the three treatments exerted the same level of toxicity towards the embryos. This shows that the heat treatments employed did not significantly affect the level of toxicity of cabbage on the embryos. The toxic effects of the cabbage extracts were considered significant at α = 0.05 based on the National Academy of Science (NAS)/National Research Center(NRC).
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Cabbages -- Toxicity